Corrosion damage in WC–Co cemented carbides: residual strength assessment and 3D FIB-FESEM tomography characterisation. (December 2014) - Tarragó, J. M.; Fargas, G.; Jimenez-Piqué, E.; Felip, A.; Isern, L.; Coureaux, D.; Roa, J. J.; Al-Dawery, I.; Fair, J.; Llanes, L.
Abstract : The effect of corrosion damage on cemented carbides was investigated. The study included residual strength assessment and detailed fractographic inspection of corroded specimens as well as detailed 3D FIB-FESEM tomography characterisation. Experimental results point out a strong strength decrease associated with localised corrosion damage, i.e. corrosion pits acting as stress raisers, concentrated in the binder phase. These pits exhibit a variable and partial interconnectivity, as a function of depth from the surface, and are the result of heterogeneous dissolution of the metallic phase, specifically at the corrosion front. However, as corrosion advances the ratio between pit depth and thickness of damaged layer decreases. Thus, stress concentration effect ascribed to corrosion pits gets geometrically lessened, damage becomes effectively homogenised and relatively changes in residual strength as exposure time gets longer are found to be less pronounced.